Academic oncology clinicians' understanding of biosimilars and information needed before prescribing. (January 2019) - Cook, John W.; McGrath, Megan K.; Dixon, Margie D.; Switchenko, Jeffrey M.; Harvey, R. Donald; Pentz, Rebecca D.
Background: With increasing numbers of oncology biosimilars in the approval pipeline, it is important to investigate oncology clinicians' understanding of biosimilars and what information they need prior to adoption. Methods: Between January and May 2018, 77 oncology clinicians (52 physicians, 16 pharmacists, and 9 advanced practice providers) completed a survey covering three domains: clinician understanding, prescription preferences, and patient involvement. An in-depth interview was designed based on themes identified in the first 50 surveys: cost, safety and efficacy, patient preference, and disease stage. Participants were chosen to participate in the interview based on outlying responses to survey questions. Results: When asked to define a biosimilar, 74% (57/77) of respondents could not give a satisfactory definition, and 40.3% (31/77) considered a biosimilar the same as a generic drug. The most important factor in biosimilar prescription was safety and efficacy (4.51 out of 5) followed closely by cost differences (4.34 out of 5). A 40% increase (53.2–94.8%) in clinicians' prescribing likelihood was seen after a biosimilar is designated as interchangeable. Participants in this study were split regarding the importance of shared decision-making with patients [50.7% (39/77) important or extremely important, 39.0% (30/77) somewhat or not at all important]. Clinicians were also split concerning the role that pharmacists should play in the decision to prescribe or substitute biosimilars. Conclusion: Understanding of biosimilars is low, and educational needs are high. The information that clinicians deem important to assess, such as safety, efficacy and cost, will need to be provided before they are comfortable prescribing biosimilars.